A Specific Distress Cutoff Score Shortly After Breast Cancer Diagnosis. Issue 3 (May 2017) - Ploos van Amstel, Floortje K.; Tol, Jolien; Sessink, Kelly H.; van der Graaf, Winette T. A.; Prins, Judith B.; Ottevanger, Petronella B.
Abstract : Background: High levels of distress are expected shortly after the diagnosis breast cancer. The Distress Thermometer (DT) is commonly used to screen for distress, using a cutoff score of 4 or 5; however, this score might not be appropriate for detecting distress in women with recently diagnosed breast cancer. Objectives: The aims of this study were to establish the optimal DT cutoff score for detecting high distress shortly after breast cancer diagnosis and to correlate this score with the reported problems. Methods: We selected for this study Dutch women who completed the DT and the Hospital Anxiety and Depression Scale within 1 month after breast cancer diagnosis. Receiver operating characteristic analysis of DT scores was performed, with the Hospital Anxiety and Depression Scale being used as the criterion standard for the level of distress. The sensitivity, specificity, positive predictive value, and negative predictive value of each DT score were calculated. Results: In total, 181 women participated in the study. The optimal DT cutoff score for detecting distress was 7 with a sensitivity of 0.73, specificity of 0.84, positive predictive value of 69%, and negative predictive value of 87%. Emotional problems were the most frequently reported concerns. Conclusion: We consider a cutoff score of 7, shortly after breast cancer is diagnosed, optimal to identify those women with high distress and therefore at risk of chronic distress. Implications for Practice: The findings are clinically important because they can enable healthcare professionals to direct their time and resources to those most in need of their assistance.